THE INFLUENCE OF INSTITUTIONAL OWNERSHIP, LEVERAGE, AND FINANCIAL DISTRESS ON TAX AGGRESSIVENESS - Ismanto, Juli; Abdurachman, Arya (Sekolah tinggi ilmu ekonomi pemuda, 2024)
This study was inspired to look at the factors that influence the practice of tax aggressiveness seen in financial factors and corporate governance. The research was then developed by proving other factors that strengthen the importance of the company's information breadth in eliciting a response from the market that can affect the level of tax aggressiveness, namely financial distress. The object of this research is companies in the Real Estate & Property Services Sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The samples taken from this study were taken using the purposive sampling method, which resulted in a total of 15 companies for 4 years. The results of research on institutional ownership, leverage, and financial distress on tax aggressiveness can be concluded that institutional ownership and leverage have no effect on tax aggressiveness, while financial distress affects tax aggressiveness with a negative coefficient direction, proving empirically that when companies face financial difficulties, their top priorities tend to maintain liquidity and meet urgent financial obligations.